2020
DOI: 10.3390/nu12092729
|View full text |Cite
|
Sign up to set email alerts
|

Protein Supplementation Enhances the Effects of Intermittent Loading on Skeletal Muscles by Activating the mTORC1 Signaling Pathway in a Rat Model of Disuse Atrophy

Abstract: Inactivity leads to skeletal muscle atrophy, whereas intermittent loading (IL) during hind limb unloading (HU) attenuates muscle atrophy. However, the combined effects of IL and protein supplementation on disuse muscle atrophy are unclear. Therefore, we investigated the effects of IL and a high-protein oral nutritional supplement (HP) during HU on skeletal muscle mass and protein synthesis/breakdown. Male F344 rats were assigned to the control (CON), 14-day HU (HU), IL during HU (HU + IL), and IL during HU fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Importantly, the response of muscle hypertrophy did not differ between the groups [247], showing that disuse muscle atrophy does not alter muscle protein synthesis in response to acute resistance exercise and muscle hypertrophy in response to chronic resistance training. Consistent with these data, another study on disuse atrophy showed that intermittent loading with protein ingestion prevents atrophy during hindlimb unloading probably through mTORC1 signaling pathway [248].…”
Section: Impact Of Exercise Training and Practical Recommendationssupporting
confidence: 69%
“…Importantly, the response of muscle hypertrophy did not differ between the groups [247], showing that disuse muscle atrophy does not alter muscle protein synthesis in response to acute resistance exercise and muscle hypertrophy in response to chronic resistance training. Consistent with these data, another study on disuse atrophy showed that intermittent loading with protein ingestion prevents atrophy during hindlimb unloading probably through mTORC1 signaling pathway [248].…”
Section: Impact Of Exercise Training and Practical Recommendationssupporting
confidence: 69%
“…The ubiquitin–proteasome and autophagy–lysosome systems play key roles in protein degradation during muscle atrophy [ 14 , 15 , 16 ]. The upregulation of ubiquitin ligases and autophagy-related mRNA or protein expression was observed in animal models of muscle disuse and human bed rest conditions [ 15 , 29 , 35 , 36 , 37 , 38 ]. In this study, we measured mRNA expressions of atrogenes (Atrogin-1, MuRF1), autophagy-related genes (ULK1, LC3B, p62, Gabarap, and Bnip3), and FOXO transcription factors (Foxo1, Foxo3, and Gadd45a) which control both systems [ 17 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, further evaluation is needed to confirm the fiber type-specific effect of AA and/or Exc. Second, the intermittent loading of Exc was conducted according to the methods proposed in previous studies [ 29 , 30 ]; however, it was difficult to obtain a unified Exc volume in individual animals. Hence, the combined effects of Exc itself may be altered depending on the individual and study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein, amino acid, and peptides supplementation (Table 1) is considered to be effective in increasing muscle anabolism and preventing muscle atrophy during extended periods of immobilization [19]. Oral administration of a high protein liquid nutritional supplement (milk protein, whey protein, leucine, and citrulline) inhibits intermittent loadinginduced muscle atrophy and increases muscle mass by activating the mTORC1 signaling pathway (Ribosomal protein S6 kinase (p70S6K) and ribosomal protein S6 (rpS6)) [20]. Shin et al reported that soluble whey protein hydrolysate increases grip strength, muscle mass, and cross-sectional area of muscle fiber and meliorates immobilization-induced C57BL/6 mice muscle atrophy via regulating the PI3K/Akt pathway [21].…”
Section: Protein Amino Acid and Peptidesmentioning
confidence: 99%